The Role of City Diplomacy for Sustainable Environment : Study Case of River Restoration in Bandung - Muluk, MR. Khairul; Indaswari, Firstyarinda Valentina; Wiswayana, Wishnu Mahendra; Yunita, Primadiana (KnE Social Sciences, 2022)
The concept of sister cities as a cooperation mechanism for sub-national actors has been spread and grown significantly for these 70 years. The issues covered can involve not only economics and culture but also the sustainability of the environment. As the world faces extreme climate change challenges, cities become the most vulnerable areas. This paper examined the role of city diplomacy between Bandung and Seoul concerning the restoration of Cikapundung river. How strategic was this cooperation scheme in promoting a better environment and preservation as both cities have large populations and modern lifestyles? The research used qualitative method through a study case. The data were collected through secondary resources, such as government documents, journals, and databases. The analysis found that city diplomacy has a strategic role in solving the primary problem of river damage. Both governments collaborated with other actors to rehabilitate the river. Unfortunately, there was no ongoing sustainable cooperation to preserve the river. There are still more stages that need to be completed to fulfill the standard of river management. We hope there will be sustainable cooperation to support a sustainable environment in the future as the impact could be directly felt by all the living beings within it. Keywords: Bandung; environment; river management; sister city; Seoul